Integration of Halal Standards and Cultural Competence: A Comprehensive Analysis of Restaurant Business Management in Thailand's Multicultural Context - Tangkham, Phunphiphat (Journal of Ecohumanism, 2024)
This study investigates the complex interplay between Halal certification compliance and multicultural service delivery in restaurant operations within Pattani Province, Thailand. Using a quantitative approach with a sample of 303 restaurant owners and staff, the research examines how religious adherence, cultural competence, and business practices influence operational success in a diverse cultural environment. The study employs structural equation modeling to analyze relationships between staff characteristics, management practices, and business outcomes. Findings reveal significant correlations between cultural integration and business success (β = 0.832, p < 0.001), with education level and management effectiveness showing strong positive relationships (β = 0.412, p < 0.001). The research demonstrates that successful integration of Halal standards with cultural sensitivity significantly enhances customer satisfaction and business growth, explaining 84.5% of variance in business success measures. These findings contribute to understanding how religious compliance and cultural competence can be effectively balanced in restaurant management, offering practical implications for industry practitioners and policymakers in multicultural contexts.